High-temperature-corrosion-resistant anodic oxide film as well as preparation process and application thereof
By using an improved anodic oxidation film preparation process in OLED preparation and using an electrolyte composed of oxalic acid and citric acid for anodization, the problem of insufficient heat resistance of the anodic oxide film at high temperatures in the existing technology has been solved, and higher performance has been achieved. The heat resistance and corrosion resistance improve the service life of the equipment and the yield rate of finished products.
Patent Information
- Application Number
- CN202411463753.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
In the chemical vapor deposition chamber used in the OLED preparation, the anodic oxide film is not heat-resistant enough during high temperature and continuous thermal shock, resulting in film cracking and falling off to produce particulate matter, and the corrosion resistance is insufficient, affecting the yield of the finished product.
The anode oxidation is performed at 15-25 ° C and the current density is 0.1A/DM2 ~ 0.4A/DM2. The electrolyte is composed of oxalic acid and citric acid. The concentration of oxalic acid is 15 g/L to 25g/L. The concentration is 25g/L to 35g/L. By improving process parameters, it is used to prepare high -temperature corrosion anode oxide film.
It improves the heat resistance and corrosion resistance of the anode oxide film, reduce the cracking of the membrane and the production of particulate matter, extend the service life of the equipment, and increase the yield of the finished product.
Smart Images

Figure CN119332323A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic coating for forming a conversion layer, and in particular, relates to an anodic oxide film resistant to high temperature corrosion and a preparation process and application thereof. Background Art
[0002] Organic Light Emitting Diode (OLED) is an advanced display technology. OLED display screens are composed of multi-layer organic thin film structures. When current passes through them, these organic materials emit light, so they have self-luminous properties. The reason why OLED technology can be widely used is that compared with other technologies, it has the following advantages: (1) low power consumption; (2) fast response speed; (3) wide viewing angle; (4) high-resolution display; (5) wide temperature characteristics; (6) OLED can achieve soft screen; (7) OLED finished products are relatively light. OLED is currently produced on the 6th generation production line. The process temperature of its Chemical Vapor Deposition (CVD) process is often 380℃~420℃. At the same time, the chamber has higher requirements for particles. To prevent the diffuser spare parts from arcing and particles in high temperature and corrosive environments, special anodizing surface treatment is often required to improve its corrosion resistance and high temperature resistance. At present, the diffuser in the OLED organic light-emitting diode chemical vapor deposition chamber (OLED CVD Chamber) is often used for more than one year and the chamber needs to be switched frequently for equipment replacement. During the frequent heating and cooling process, the oxide film is continuously subjected to thermal shock. The thermal expansion coefficient of aluminum alloy is higher than that of the oxide film on its surface, and tensile stress will be generated in the oxide film during the heating process. When the tensile stress inside the film exceeds the tensile strength of the film, critical cracking will occur, and the oxide film will fall off and fall into the chamber, resulting in poor particle indicators. Poor particle indicators are the main reason affecting the yield of the chemical vapor deposition process. Therefore, improving the heat resistance of the oxide film has always been a difficult problem in the industry.
[0003] The existing organic light-emitting diode diffuser (OLED Diffuser) production technology mainly uses oxalic acid electrolyte to perform anodization at a higher current density. The generated anodized film has slightly lower high temperature resistance and corrosion resistance, insufficient stability in use, and the oxide film is prone to cracking and corrosion by corrosive gases from the client. For example, the Chinese invention patent publication number CN114717628A, the application date is April 14, 2022, and the invention name is "A method for preparing an anodized film". The disclosed preparation method includes degreasing treatment, alkaline etching treatment, neutralization treatment, anodizing treatment, ultrasonic cleaning treatment and sealing treatment in sequence. By improving the process parameters, a mixed acid anodizing of 6g / L~40g / L oxalic acid and 14g / L~16g / L sulfuric acid is used to recombine the basic operations. Although this solution improves the corrosion resistance and voltage resistance of the film and solves the corrosion problem of the anodized film on the surface of the components of the vacuum dry etching equipment for OLED, it is not resistant to high temperatures. When the oxide film is continuously subjected to thermal shock, it will fall off, causing particle pollution and affecting the product yield.
[0004] Another example is the Chinese invention patent publication number CN115772697A, the application date is July 26, 2022, and the invention name is "An anodic oxidant, oxidation process and oxide film applied to a gas diffuser". The disclosed oxidant includes a main liquid with a mass fraction of 3% to 8%, a main additive with a mass fraction of 0.5% to 2%, and a secondary additive with a mass fraction of 0% to 2%. The main liquid is oxalic acid, the main additive is citric acid, and the secondary additive is tartaric acid or polyethylene glycol. The anodizing process of the gas diffuser using the above-mentioned oxidant is also disclosed. The corrosion resistance of the finally obtained anodized film is increased and can withstand thermal shock, but the anodized film of this scheme is applied to LCDs, and its preparation process does not meet the extreme heat resistance requirements of OLEDs. For the preparation of LCDs and OLEDs, the temperature requirements of the two in the CVD process are different. In the preparation process of LCDs, the CVD technologies commonly used include plasma enhanced chemical vapor deposition (PECVD) and low pressure chemical vapor deposition (LPCVD), which can be carried out at relatively low temperatures, usually between 250 and 350 ° C. OLEDs are usually made by thermal evaporation or metal organic chemical vapor deposition (MOCVD), which require higher temperatures to ensure the evaporation and deposition of organic materials. The CVD temperature in the OLED preparation process is usually between 380°C and 420°C. Summary of the invention
[0005] 1. Problems to be solved
[0006] In view of the technical problem that the chemical vapor deposition chamber used for OLED preparation in the prior art uses diffusers and other components that require anodizing regeneration, the film has insufficient heat resistance during high temperature and continuous thermal shock, resulting in film cracking and shedding to produce particles, and insufficient corrosion resistance, resulting in arc discharge, which affects the yield of finished products. This application provides a preparation process for high temperature corrosion resistant anodized film, which prepares anodized film, solves the problem of cracking due to temperature rise and fall, improves corrosion resistance, and increases the service life of the equipment.
[0007] 2. Technical solution
[0008] In order to achieve the above purpose, the technical solution provided is:
[0009] The preparation process of the high temperature corrosion resistant anodized film includes the following steps: degreasing, first water washing, alkaline etching, second water washing, neutralization, anodizing and cleaning, using an electrolyte at 15-25°C and a current density of 0.1A / dm 2 ~0.4A / dm 2 Anodizing is performed under
[0010] The electrolyte consists of oxalic acid and citric acid, the concentration of the oxalic acid is 15 g / L to 25 g / L, and the concentration of the citric acid is 25 g / L to 35 g / L.
[0011] Furthermore, the concentration of the oxalic acid is 20 g / L, and the concentration of the citric acid is 30 g / L.
[0012] Furthermore, the current density is 0.1A / dm 2 ~0.2A / dm 2 .
[0013] Furthermore, the current density is 0.2A / dm 2 .
[0014] Furthermore, the degreasing adopts a degreasing agent with a concentration of 50g / L to 60g / L.
[0015] Furthermore, the alkaline etching uses NaOH with a concentration of 40 g / L to 60 g / L.
[0016] Furthermore, the neutralization uses HNO3 with a concentration of 100g / L to 300g / L.
[0017] The high temperature corrosion resistant anodic oxide film is prepared by the process.
[0018] Application of high temperature corrosion resistant anodized film: applying the high temperature corrosion resistant anodized film to the preparation of OLED.
[0019] 3. Beneficial effects
[0020] Compared with the existing known technology, the technical solution provided by the present invention has the following beneficial effects:
[0021] (1) The preparation process of the high temperature corrosion resistant anodized film of the present invention uses an electrolyte at 15 to 25°C and a current density of 0.1 A / dm 2 ~0.4A / dm 2 The anodizing is carried out under the condition that the electrolyte is composed of oxalic acid and citric acid, the concentration of oxalic acid is 15g / L-25g / L, and the concentration of citric acid is 25g / L-35g / L. Adding citric acid electrolyte on the basis of oxalic acid can reduce the pore diameter of the oxide film, make the oxide film denser, and enhance the corrosion resistance. By improving the process parameters of the anodizing process (electrolyte composition, electrolysis temperature, current density), a preparation process of an anodized film resistant to high temperature corrosion is obtained.
[0022] (2) The high temperature corrosion resistant anodized film of the present invention has a greatly reduced membrane pore diameter, strong density, uniform membrane thickness, high heat resistance and high corrosion resistance. It will not generate arcs and particulate matter under high temperature (500°C) and corrosive conditions, thereby improving the yield of the finished product.
[0023] (3) The application of the high temperature corrosion resistant anodized film of the present invention in the preparation of OLED has good operation conditions on the client side, thus improving the life of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a comparison chart of the acid corrosion resistance test of the oxide film prepared by the electrolytes with different components in Example 1;
[0025] Figure 2 This is a comparison chart of the alkali corrosion resistance test of the oxide film prepared by the electrolytes with different components in Example 1;
[0026] Figure 3 A comparison chart of the thermal shock times of the oxide films prepared at different current densities in Example 3;
[0027] Figure 4 This is a comparison chart of the acid corrosion resistance test between the process of Example 4 and the original process;
[0028] Figure 5 This is a comparison chart of the alkali corrosion resistance test between the process of Example 4 and the original process;
[0029] Figure 6 It is a comparison chart of the number of thermal shocks between the process of Example 4 and the original process;
[0030] Figure 7 It is equipment for thermal shock testing;
[0031] Figure 8 This is a corrosion resistance test diagram;
[0032] Fig. 9 Make equipment for anodizing test pieces;
[0033] Fig.10 Hanging status diagram for OLED diffuser. DETAILED DESCRIPTION
[0034] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.
[0035] Example 1
[0036] The high temperature corrosion resistant anodized film preparation process of this embodiment includes the following steps:
[0037] S1 Check the appearance, size and flatness of the product. If the flatness meets the requirements, the dirt and oxide film on the surface of the product can be directly peeled off. If the flatness does not meet the requirements, flatness correction must be performed first, that is, shaping through heat treatment or oil pressure before peeling;
[0038] S2 is polished as a whole by mechanical grinding to remove surface damage;
[0039] S3 performs sandblasting operations;
[0040] S4 sequentially performs degreasing, first water washing, alkaline etching, second water washing, neutralization, and cleaning operations on the product. The concentration of the degreasing agent is 55g / L, and the degreasing agent composition is 50% sodium phosphate dodecahydrate, 30% sodium silicate pentahydrate, 15% sodium carbonate, and 5% surfactant, which can remove surface grease. Alkaline etching uses 50g / L NaOH to remove surface impurities, and neutralization uses 200g / L HNO3;
[0041] S5: Place the product in an electrolyte for anodization. The composition of the electrolyte is shown in Table 1. The anode temperature is 15°C and the current density is 0.5A / dm 2 ;
[0042] S6 washes and dries the anodized product and performs a performance test. The performance test results are shown in Table 1. Figure 1 and Figure 2 .
[0043] Corrosion resistance test: The anodized product was placed in 50g / L HCL or 1mol / L NaOH for corrosion resistance test. The initial state was clear and transparent. After a period of time, bubbles began to appear, and finally white bubbles appeared evenly. The time when the uniform white bubbles began to appear was recorded (see Figure 8 ).
[0044] Thermal shock test: Place the anodized product into a thermal shock test device (manufacturer: Shanghai Jujing, model: SXL-1200C, see Figure 7 ) and record the number of times it is subjected to thermal shock at 500°C.
[0045] Table 1 Electrolyte composition adjustment test
[0046] Serial number Electrolyte (g / L) Corrosion resistance (HCL) Corrosion resistance (NaOH) Thermal shock times Blank Oxalic acid 40 15min 21s 3 a Oxalic acid 40, citric acid 10 18 min 26s 4 b Oxalic acid 40, citric acid 20 22 min 38s 3 c Oxalic acid 40, citric acid 30 25 min 41s 2 d Oxalic acid 30, citric acid 30 30 min 48s 3 e Oxalic acid 15-25, citric acid 25-35 36 min 60s 3
[0047] The surface morphology and performance of anodized films prepared with different electrolyte compositions are different. The traditional oxalic acid film has larger pores and adsorbs more particulate matter, making it easier for corrosive gases to penetrate into the pores, resulting in poor corrosion resistance of the oxide film. Adding citric acid electrolyte to oxalic acid can greatly reduce the pore diameter of the oxide film, making the oxide film denser and more corrosion-resistant. The concentrations of oxalic acid and citric acid in the electrolyte were further explored, and the corrosion resistance of the anodized film in acid or alkali was tested.
[0048] According to the experimental results in Table 1, the corrosion resistance of No. e is the best. At this time, the electrolyte composition is 15-25 g / L oxalic acid and 25-35 g / L citric acid, but the heat resistance is not significantly improved.
[0049] Example 2
[0050] The preparation process of the high temperature corrosion resistant anodized film of this embodiment is basically the same as that of embodiment 1, except that:
[0051] S5: Place the product in an electrolyte of 40 g / L oxalic acid for anodization. The anode temperature is shown in Table 2. The current density is 0.5 A / dm 2 ;
[0052] S6 washes and dries the anodized product and performs a performance test. The performance test results are shown in Table 2.
[0053] Table 2 Anode temperature (i.e. electrolysis temperature) test
[0054] Serial number Anode temperature (℃) Corrosion resistance HCL(min) Corrosion resistant NaOH(s) Thermal shock times Blank 15 15 21 3 a 10 18 20 1 b 20 14 18 7 c 25 12 20 Powdering d 30 13 22 Powdering
[0055] Note: The thermal shock times are tested at 500°C.
[0056] During the anodizing process, a constant current is mostly used. As the anodizing process continues, the thickness of the oxide film continues to increase, and its insulation performance is enhanced. In order to stabilize the current, the voltage will continue to increase. In this process, a large amount of heat will be released, causing the oxide film to dissolve faster in the electrolyte and the film formation rate to slow down. The oxide film generated by low anode temperature has strong corrosion resistance, hardness, and wear resistance, but poor heat resistance. On the contrary, by increasing the anode temperature, the corrosion resistance, hardness, and wear resistance of the oxide film will decrease accordingly, and its heat resistance will be enhanced. Traditionally, oxalic acid films mostly use 15°C as the electrolysis temperature. By increasing the electrolysis temperature, the heat resistance of the test piece was tested at 450°C, but it failed to meet the extreme heat resistance requirements of OLED.
[0057] According to the anode temperature test results in Table 2, it can be concluded that due to the high temperature of the anodes c and d, the oxide film is powdered. Considering the oxide film state and heat resistance, the performance of b is best when the temperature is 20℃, but the corrosion resistance is not significantly improved.
[0058] Example 3
[0059] The preparation process of the high temperature corrosion resistant anodized film of this embodiment is basically the same as that of embodiment 1, except that:
[0060] S5: The product is placed in an electrolyte for anodization. The electrolyte composition is 40 g / L oxalic acid, the anode temperature is 15°C, and the current density is shown in Table 3;
[0061] S6 washes and dries the anodized product and performs a performance test. The performance test results are shown in Table 3 and Figure 3 .
[0062] Table 3 Current density test
[0063] Serial number Current density Corrosion resistance (HCL) Corrosion resistance (NaOH) Thermal shock times Blank <![CDATA[0.5A / dm 2 ]]> 15min 21s 3 a <![CDATA[0.4A / dm 2 ]]> 17min 24s 5 b <![CDATA[0.3A / dm 2 ]]> 13min 18s 5 c <![CDATA[0.2A / dm 2 ]]> 15min 26s 7 d <![CDATA[0.1A / dm 2 ]]> 12min 18s 6
[0064] Note: The thermal shock times are tested at 500°C.
[0065] Changes in current density will affect the density, film formation rate, film uniformity and heat resistance of the oxide film. In the prior art, the required performance is generally achieved by increasing the current density. The Chinese invention patent publication number is CN114717628A, the application date is April 14, 2022, and the invention name is "A method for preparing an anodic oxide film". The current density used is 0.5A / dm 2 ~1.5A / dm 2 In this embodiment, by reducing the current density, an oxide film with more uniform film thickness and higher heat resistance can be obtained. The hardness of the oxide film is relatively low and the film forming rate is slow.
[0066] According to the current density test in Table 3, the serial number c can be obtained, that is, the current density is 0.2A / dm2 When the thermal shock performance is the best, but the corrosion resistance is not significantly improved.
[0067] Example 4
[0068] The preparation process of the high temperature corrosion resistant anodized film of this embodiment is basically the same as that of embodiment 1, except that:
[0069] S5 puts the product into the electrolyte for anodization. The electrolyte composition is 20g / L oxalic acid and 30g / L citric acid. The anode temperature is 15-25℃ and the current density is 0.2A / dm 2 .
[0070] S6 washes and dries the anodized product and performs a performance test. The performance test results are compared with the original process (oxalic acid 40g / L, temperature 15°C) and are shown in Table 4. Figure 4-6 .
[0071] Table 4 Comparison between the original process and this embodiment
[0072]
[0073] Note: The thermal shock times are tested at 500°C.
[0074] It can be seen from Table 4 that the anodized film prepared in this embodiment has greatly improved corrosion resistance and high temperature resistance, and the thermal shock resistance is the best under 500°C.
[0075] It can be seen from Examples 1-4 that in the preparation process of the high temperature resistant and corrosion resistant anodized film, the electrolyte composition is: 20 g / L oxalic acid and 30 g / L citric acid, the anode temperature is 15-25°C, the current density is 0.2 A / dm 2 The prepared anodized film has excellent performance. The anodized test piece production equipment used in this application is as follows Fig. 9 As shown, it is applied to the OLED diffuser (such as Fig.10 ), the machine is in good condition at the client, which greatly improves the customer's yield rate and extends the machine life.
[0076] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person skilled in the art, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. The preparation process of high temperature corrosion resistant anodized film comprises the following steps: Degreasing, first water washing, alkaline etching, second water washing, neutralization, anodizing and cleaning, characterized in that: the electrolyte is used at 15-25°C and the current density is 0.1A / dm 2 ~0.4A / dm 2 Anodizing is performed under The electrolyte consists of oxalic acid and citric acid, the concentration of the oxalic acid is 15 g / L to 25 g / L, and the concentration of the citric acid is 25 g / L to 35 g / L.
2. The process for preparing the high temperature corrosion resistant anodic oxide film according to claim 1, characterized in that: The concentration of the oxalic acid is 20 g / L, and the concentration of the citric acid is 30 g / L.
3. The process for preparing the high temperature corrosion resistant anodic oxide film according to claim 2, characterized in that: The current density is 0.1A / dm 2 ~0.2A / dm 2 .
4. The process for preparing the high temperature corrosion resistant anodic oxide film according to claim 3, characterized in that: The current density is 0.2A / dm 2 .
5. The process for preparing a high temperature corrosion resistant anodic oxide film according to any one of claims 1 to 4, characterized in that: The degreasing process uses a degreasing agent with a concentration of 50 g / L to 60 g / L.
6. The process for preparing the high temperature corrosion resistant anodized film according to claim 5, characterized in that: The alkaline etching uses NaOH with a concentration of 40 g / L to 60 g / L.
7. The process for preparing the high temperature corrosion resistant anodic oxide film according to claim 6, characterized in that: The neutralization uses HNO3 with a concentration of 100g / L to 300g / L.
8. High temperature corrosion resistant anodized film, characterized by: The invention is prepared by the process according to any one of claims 1 to 7.
9. Application of high temperature corrosion resistant anodized film, characterized by: The high temperature corrosion resistant anodized film according to claim 8 is applied to the preparation of OLED.
Citation Information
Patent Citations
A composite of anodizing electrolyte for alloyedaluminum and therefor composite method
KR1020050065497A
Method for anodizing surface treatment for film formation having high resistance to thermal shock
KR102143590B1